Sources of stress in NCAA Division I women ice hockey players - Heller, T. L.; Bloom, G. A.; Neil, G. I.; Salmela, J. H. (Athletic Insight - The Online Journal of Sport Psychology, 2005)
The purpose of this study was to identify the sources of stress experienced by NCAA Division I women ice hockey players. Individual interviews consisting of open-ended questions were carried out with six elite athletes. The results of the qualitative analysis identified three main categories of stress: (a) hockey pressures, which included the transition to and the advantages of playing Division I hockey, as well as performance stressors and training concerns, (b) relationship issues, which included the athletes` concerns with relationships in their personal lives, and (c) educational demands, which included academic and time concerns relating to their studies. The results of this study revealed that the primary source of stress emanated from the game itself and adapting to higher expectations, intense scrutiny, and higher caliber of play.